The cookie fiasco - Santat, Dan 1975-; Willems, Mo 1968- (Hyperion Books for Children, 2016)
"There are only three cookies and four hungry friends to share them with. This is not good. This is not equal!"...
Keywords: JUVENILE FICTION / Humorous Stories / bisacsh; JUVENILE FICTION / Concepts / General / bisacsh; JUVENILE FICTION / Social Issues / Values & Virtues / bisacsh; Sharing; Division; Cookies; Friendship; Animals; Humorous stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Concepts / General; JUVENILE FICTION / Social Issues / Values & Virtues; Bilderbuch